Comparison of Bloodmeal Digestion and the Peritrophic Matrix in Four Sand Fly Species Differing in Susceptibility to Leishmania donovani - Pruzinova, Katerina; Sadlova, Jovana; Seblova, Veronika; Homola, Miroslav; Votypka, Jan; Volf, Petr (PloS one, 2015)
The early stage of Leishmania development in sand flies is closely connected with bloodmeal digestion. Here we compared various parameters of bloodmeal digestion in sand flies that are either susceptible (Phlebotomus argentipes and P. orientalis) or refractory (P. papatasi and Sergentomyia schwetzi) to Leishmania donovani, to study the effects on vector competence. The volume of the bloodmeal ingested, time of defecation of bloodmeal remnants, timing of formation and degradation of the peritrophic matrix (PM) and dynamics of proteolytic activities were compared in four sand fly species. Both proven vectors of L. donovani showed lower trypsin activity and slower PM formation than refractory species. Interestingly, the two natural L. donovani vectors strikingly differed from each other in secretion of the PM and midgut proteases, with P. argentipes possessing fast bloodmeal digestion with a very high peak of chymotrypsin activity and rapid degradation of the PM. Experimental infections of P. argentipes did not reveal any differences in vector competence in comparison with previously studied P. orientalis; even the very low initial dose (2×103 promastigotes/ml) led to fully developed late-stage infections with colonization of the stomodeal valve in about 40% of females. We hypothesise that the period between the breakdown of the PM and defecation of the bloodmeal remnants, i.e. the time frame when Leishmania attach to the midgut in order to prevent defecation, could be one of crucial parameters responsible for the establishment of Leishmania in the sand fly midgut. In both natural L. donovani vectors this period was significantly longer than in S. schwetzi. Both vectors are equally susceptible to L. donovani; as average bloodmeal volumes taken by females of P. argentipes and P. orientalis were 0.63 μl and 0.59 μl, respectively, an infective dose corresponding to 1-2 parasites was enough to initiate mature infections.
Keywords: Psychodidae; Feces; druhová specificita; Proteolysis; proteolýza; Digestion; Leishmaniasis, Visceral; přijímání potravy; leishmanióza viscerální; membrány; Disease Susceptibility; Membranes; hmyz - vektory; Eating; Species Specificity; Blood; Animals; ženské pohlaví; Leishmania donovani; zvířata; Insect Vectors; krev; náchylnost k nemoci; Female; feces; trávení